Transer towards economic substance over the legal form and its role in improving the quality of financial reporting. - عبد الحليم صفوان قصي; صخر نجاة حميد (Journal of Economics and Administrative Sciences, 2025)
The follower of the needs of the users of accounting information notices the necessity of adopting faithful representation of information Hence, IASB adopted the economic substance approach as the basis for the Formulation and development of international accounting standards Therefore, this research discusses the reflection of the economic phenomenon in terms of its economic substance on the subject of measurement , And it should be consistent measurement method where the problem of research is concentrated in the fact that the economic units operating in the local environment to address events and economic phenomena according to the legal form , as appropriate With the requirements of the unified accounting system and in line with the objectives of the economic plan of a central nature, which negatively affects the credibility and quality of financial reporting , And thus reflected on the decisions of other users of financial reports, Therefore, the research aims to highlight the concept of economic substance over the legal form, among the most prominent standards are the two (IAS Inventory & lease IFRS 16) The research has shown a contrast between the substance and form Through the beneficiaries, accounting organization, the basis of the theory, the basis of measurement, disclosure requirements, flexibility, orientation , representativity, objective, setting standards, professional judgment, imposition of currency value, expression, Management, capital preservation.